The Development of Expeller for Kernel based Seed and its Oil Characterization - SAMUEL, Olusegun David; Emovon, Ikuobase (International Journal of Integrated Engineering, 2018)
As palm kernel oil (PKO) is underexploited and the rural-based oil extraction equipment has a low efficiency in Nigeria, a performance of screw expeller designed for palm kernel oil seed extraction and suitability of the PKO for biodiesel production is presented. The expeller is modified in such a way that the expulsion unit and palm kernel cake section are carried out simultaneously thereby minimizing tardy time and boosting productivity. The key principal units of the machine are hopper, upper and lower barrel, hand wheel. The expeller is robust and easy to operate. The efficiency of the expeller and production capacity were detected to be 60.3% and 35 kg/h, respectively. The fuel physical properties of the palm kernel oil agreed with those of previous researchers but higher than those of ASTM and EU specifications. The adapted oil expeller is feasible for the extraction of oil from PKS for biodiesel production.